Efficacy of different therapeutic regimens for acute foot rot in adult sheep - Ansari, Mohammad Moin; Dar, Khadim Hussain; Tantray, Hilal Ahmad; Bhat, Mohammad Mansoor; Dar, Shahid Hussain; Naikoo, Mehraj ud-Din (Journal of Advanced Veterinary and Animal Research, 2014)
In this study, efficacies of different therapeutic regimens along with 10% zinc-sulfate footbath for the treatment of acute foot rot in adult sheep were evaluated. The research work conducted on the adult sheep (n=104) of both sexes which were presented to the Teaching Veterinary Clinical Complex during April 2013 to May 2014. Foot rot was confirmed based on clinical and physical examinations. The sheep were divided into four equal groups; G-I, G-II, G-III, and G-IV. The animals of the G-I, II and IV were treated with a mixture of amoxicillin and cloxacillin at 15 mg/kg body weight (b.wt.) through intramuscular (IM) route, oxytetracycline at 20 mg/kg b.wt., IM, and enrofloxacin at 5 mg/kg b.wt., IM, respectively. The animals of G-III were treated with gamma benzene hexachloride cream. Along with the above treatments, all four groups were given footbath with 10% zinc-sulfate. Mean recovery time (days) was recorded as lowest in G-II (3.83±0.64) followed by G-I (4.17±0.31), G-IV (4.38±0.0.79) and G-III (5.67±0.98), respectively. The mean±SE values of rectal temperature and ruminal motility that were recorded before and after the treatment showed significant (p<0.05) differences. In conclusion, administration of parenteral antibiotics in combination with footbath was highly effective to treat combination with footbath was highly effective to treat the acute foot rot in sheep. DOI: http://dx.doi.org/10.5455/javar.2014.a16 J. Adv. Vet. Anim. Res., 1(3): 114-118, September 2014